NETWORK SUITABILITY STUDY FOR TRANSMISSION LINE SLOPE MONITORING USING GIS-BASED TECHNIQUE - Mustafa I.S.; Deros S.N.M.; Din N.M.; Haroun F.M.E. (Taylor's University, 2023)
Transmission line slope monitoring is crucial to the electricity utility company in ensuring an uninterruptable power supply to the public. Common practice in slope monitoring is by deploying appropriate sensors that can automatically detect displacement or anomalies of the slopes. Sensor data were collected electronically via wireless communications and distributed through a communication network to a centralized location (base station) for data processing. Such system relied heavily on communication stability at the slope area. However, in a challenging terrain, the communication tasked becomes daunting and raised the need to hop the data from one site to the other until a site with a telecommunication coverage is found. Hence, the requirement of optimized location determination is becoming an important measure. This study proposes a site suitability identification technique for base station placement in transmission line slope monitoring to ensure uninterrupted communications. The GIS-based technique using Weighted Linear Combination for generating a suitability map with standardized Fuzzy Membership functions and Analytical Hierarchy Process were designed and applied in this study. This had been done by assigning the weightage of each contributing factor such as the network coverage, slope, elevation and land use. A case study was conducted in Cameron Highland, Malaysia. From this study, 7 sites for base station location placement were identified and they can cover the length of the transmission line at the study area. For future study and application, this methodology can be used for other remote network suitability identification analysis. School of Engineering, Taylor's University.